Preparation of hyperbranched 4-dimethylaminopyridine catalyst for the efficient synthesis of vitamin E succinate - Li, Haining; Zhang, Tiantian; Tang, Kai; Li, Binglin; Zhang, Xiaoli; Zhao, Binxia; Wang, Jiao (Comptes Rendus. Chimie)
Sorbitol was employed as the grafting agent to modify nano-silica by the hyperbranched reaction. The obtained carrier was further used to prepare immobilized 4-dimethylaminopyridine (DMAP), which was successfully applied to produce vitamin E succinate. Two crucial steps were systematically investigated during the preparation of hyperbranched loaded DMAP: the epoxy-alcohol addition and N-alkylation reactions. For the epoxy-alcohol addition reaction, the maximum hydroxyl content reached 8.89 mmol/g when the molar ratio of sorbitol to epoxide was 2.5:1, the reaction temperature was 55 °C, the stirring rate was 500 rpm, and the reaction time was 8 h. In the N-alkylation reaction, when the reaction time was 20 h, the reaction temperature was 130 °C, the molar ratio of MAP to K$_{2}$CO$_{3}$ was 1:1.5, the KI to MAP molar ratio was 1:1 and the stirring rate was 600 rpm, the highest loading of DMAP reached 5.17 mmol/g. The catalytic performance of the loaded DMAP with different branching levels was evaluated by the acetylation reaction. The highest catalytic activity was observed in the hyperbranched catalyst, which reached 24.97 mmol/h${· }$g. Moreover, the stability of the prepared immobilized DMAP was significantly enhanced. After being used for ten batches, 94.9% of the catalytic activity retention rate was obtained.